The Use of ELSA Application in Teaching Pronunciation - Mila, Nyak; Fitria, Nora (English LAnguage Study and TEaching, 2024)
ELSA is an application that can detect pronunciation errors. This research aims to find out whether using the Elsa application can improve students' pronunciation. The samples used were 40 students in grades 2 and 3 of SMP N 1 Beutoeng Ateuh; 20 from class 2, and 20 from class 3. Data collection used pre-tests, post-tests and experiments. The data analysis used is the Homogeneity Test, Paired Sample T-Test and Independent T-Test. Homogeneity Test findings indicate that the sample groups are similar enough to be comparable. The results of the Paired Sample T-Test showed a significant improvement in students' pronunciation skills after using the ELSA application, which highlights the effectiveness of the application in assisting pronunciation learning. The Independent T-Test further supports these findings by showing a striking difference in pronunciation skills between the experimental group that used the ELSA application and the control group that did not use the ELSA application.